Improved Cryopreservation of Boer Goat Semen - Soe, Win Naing (2010)
Recently, interest in the cryopreservation of spermatozoa as a potential source of valuable genes has escalated to improve reproductive efficiency and productivity in livestock such as goats. The objectives of this study were to improve the quality of semen cryopreservation media, technique of cryopreservation, and to analyse the effects of various factors on goat sperm survival after freezing and thawing. To conduct this research, eleven Boer goats were used and semen was collected twice a week using an artificial vagina. For initial evaluation, the semen samples were assessed for volume, colour, consistency, mass activity, sperm concentration, sperm morphology, and percentage of motile spermatozoa. The qualified semen samples between one and two mL volume with a concentration of greater than 2.5 X 10 9 sperm/mL having >75% progressively motile sperm and >85% of the sperm with normal morphology were selected for cryopreservation. The qualified ejaculates were then diluted with the semen extenders and packed in 0.25 mL. French straws. After equilibration, cooling and freezing procedures were carried out in a cooling chamber and liquid nitrogen. Two days later, the semen was thawed at 37˚C for 30 sec and evaluated for the semen qualitative parameters such as motility, acrosome integrity, membrane integrity, live and normal spermatozoa percentages. Data were analyzed using ANOVA, followed by Tukey’s post hoc test to determine significant differences in all the parameters between groups using the SPSS software system. The effects of four different sugars on semen quality were analyzed for the improvement of semen cryopreservation media in Boer goats. This study was conducted to analyze firstly the effect of two monosaccharides and two disaccharides in Boer goat semen cryopreservation, secondly, to investigate the combination effects of trehalose and other sugars, and finally to find out the most effective concentration of trehalose combination for Boer semen cryopreservation. The combination of 69.38 mM glucose and 198.24 mM trehalose conferred the practical and beneficial effects in cryopreservation of Boer goat spermatozoa. The effects of four cryoprotectants, different concentrations of glycerol and three glycerolization procedures with two cooling times for Boer goat semen cryopreservation were evaluated through analysis of motility parameters. The use of glycerol cryoprotectant at the concentration of 7% conferred the best cryoprotective effect for Boer goat semen cryopreservation. In addition, the use of three-step dilution method (mC) and three hour cooling time improved semen quality after cryopreservation. The effects of four amino acids (alanine, glycine, cysteine and glutamine) at concentrations of 20, 40, and 60 mM on semen quality were examined in Boer goat semen cryopreservation. The effect of different concentrations of cysteine (0, 5, 9.5, 15.5, 20 mM) on cryopreservation semen was subsequently evaluated to find out the optimum concentration to improve semen quality after cryopreservation. Cysteine at the concentration of 5 mM provided the most effective protection against cryodamage by improving post-thawed semen quality during cryopreservation process in Boer goat semen. Three experiments were conducted to determine the effects of seminal plasma removal using two different extenders, the effects of three different washing solutions and the effects of different centrifugation regimes on the characteristics of Boer goat semen before freezing and after thawing. This study showed that the removal of seminal plasma by centrifugation at 3000 x g for 3 min with Tris citric acid glucose washing solution in Boer goat semen cryopreservation protocol could be used to improve sperm survival in Boer goat semen cryopreservation. However, these results are based on in vitro evaluations, further fertility trials are requires as ultimate test of improved cryopreservation.